Study of the effect of geological and geomorphological parameters on soil erosion and sediment yield of Gabrik River basin, S.E Iran - Shojaei, Shahrooz; Reza Noura, Mohammad; Moslempour, Mohammad Elyas (Nexo Revista Científica, 2022)
The Gabrik River basin is located in the Makran zone in southeast of Iran. This basin is characterized by specific geomorphological features related to its geological characteristics and geographical location. The present study investigates the attempts to minimize the negative effects of sediment accumulation behind the Gabrik dam in this region. Therefore, the main objectives of this research are to study the geomorphological status of the basin and analyze the sensitivity of geological units to erosion. Investigation of geomorphological forms of the Gabrik basin indicates that the internal (tectonic) and external (erosion and sedimentary processes) dynamic processes have a significant role in the basin evolution. The results could be used to identify the potential areas for erosion and sediment production. To estimate the sediment erosion and yield, the Gabrik basin was divided into two hydrological units (i.e., HU1 and HU2). Then, the required information to determine nine factors of the MPSIAC model and five factors of the FSM model were provided and determined for each unit. Afterward, the soil erosion maps were extracted in ArcGIS software. As a result, the rate of sediment yield from MPSIAC and FSM models was determined 4 and 6.23 tons per hectares, respectively. The findings of this research indicate the importance of tectonics, lithological units, and climate on erosion rate, sediment production, and geomorphology of the Gabrik basin. Also, according to the results from erosion maps, it was revealed that the soil erodibility in the Gabrik area is low to medium. So, in these areas, the implementation of soil and water conservation programs is essential.